Inquiry in the Medical Curriculum: A Pedagogical Conundrum and a Proposed Solution. (June 2019) - Valbuena, Gustavo; O'Brien, Bridget; ten Cate, Olle; O'Sullivan, Patricia
Abstract : Habits of inquiry are considered an essential component of the modern physician's profile. These habits drive physicians to recognize and address the continuous challenges inherent to the practice of medicine; consequently, they meet the aims of better patient-centered care, better health of communities, and improved functioning of the health system. Many medical schools have endeavored to integrate inquiry into their curricula as a means of supporting development of adaptive expertise, a construct that encompasses habits of inquiry. However, the diversity of conceptualizations of inquiry has resulted in correspondingly diverse instructional implementations. Much of the emphasis has been on inquiry methods (e.g., engagement in research projects, courses in research methods and statistics), but the learners' inquiry disposition and its essential attitude component have received little attention in instruction and assessment. The authors propose that both inquiry methods and attitude need to be developed explicitly and simultaneously to prepare physicians to successfully be willing and able to address the challenges of today's health care environment. Because attitudes are established predictors of behavior, a positive inquiry attitude may be the ultimate determinant of physicians' engagement in behaviors of adaptive expertise (i.e., recognizing when learned procedures do not apply, and learning or inventing effective solutions). Addressing the attitude toward inquiry as early as possible in medical school is critical because strong attitudes are difficult to modify. Thus, a curriculum that supports positive inquiry attitude formation and strengthening will carry well beyond medical school and residency training.